Value-added tax, country governance and economic efficiency - Chan, Sok Gee; Ramly, Zulkufly; Kanapathy, Kanagi (University of Malaya Press, 2019)
Country governance and economic efficiency plays a prominent role in the government administration and the economic health of a nation in the modern economy. This includes ensuring the effective implementation of fiscal and monetary policies for the society well-being. This book focuses on the role of country governance in the implementation of Value-Added Tax (VAT) in approximately 80 percent countries in the world. Using global economic data, the finding reveals that robust country governance mitigates the regressive effect of VAT on economic efficiency. Thus, this book reaffirms the assertion that the responsibilities of the government to ensure the implementation of any tax system.